In vitro benchtop mock circulatory loop for heart failure with preserved ejection fraction emulation - Malone, Andrew; Gallagher, Sean; Saidi, Jemil; Rizq, Gina; O’Dowd, Enda; Vallence, Derek; Hameed, Aamir (Frontiers in Cardiovascular Medicine, 2022)
In this work, a novel mock circulatory loop is presented capable of simulating both healthy cardiac function and heart failure with preserved ejection fraction. This MCL differs from others presented in the literature as it features two independently actuated heart chambers, representing the left atrium and the left ventricle. This is an important improvement over other designs as it allows for potential HFpEF treatments to be examined not just in relation to their effect on the left ventricle but also on the left atrium. Two loop configurations are presented, one featuring hard PVC cylindrical chambers and one feature soft silicone chambers which are anatomically analogous to the native heart. We show that both MCLs are capable of simulating the onset of HFpEF with a sustained increase in diastolic pressure of 22.03% and a sustained decrease in end diastolic volume of 14.24%.